2008 International Conference on Complex, Intelligent and Software Intensive Systems 2008
DOI: 10.1109/cisis.2008.59
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Information System for Monitoring Student's Activity in Online Collaborative Learning

Abstract: Abstract-In this paper we address the issue of monitoring students' and groups' activity in online collaborative learning environments. This issue is especially important in the collaborative e-learning context, since an efficient monitoring process can provide valuable information to online instructors who may guide and support the development of collaborative learning projects. We have developed and tested an information system model which facilitates the automatic generation of weekly monitoring reports der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…In order to validate the previous ideas, in this section, we introduce both a prototype of a web-based structured discussion forum system, called Discussion Forum (DF) (see [4] for a detailed description of this application) and a global scheme of the monitoring system called Student Activity Monitoring using Overview Spreadsheets (SAMOS) [5], which were developed to bring new opportunities to learning by discussion and to meet new pedagogical models. We report here on this novel experience and the results achieved in the real learning context of the Open University of Catalonia.…”
Section: A Knowledge Building and Monitoring Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to validate the previous ideas, in this section, we introduce both a prototype of a web-based structured discussion forum system, called Discussion Forum (DF) (see [4] for a detailed description of this application) and a global scheme of the monitoring system called Student Activity Monitoring using Overview Spreadsheets (SAMOS) [5], which were developed to bring new opportunities to learning by discussion and to meet new pedagogical models. We report here on this novel experience and the results achieved in the real learning context of the Open University of Catalonia.…”
Section: A Knowledge Building and Monitoring Systemmentioning
confidence: 99%
“…The general functioning of this system is explain next (see [5] for a complete description and Fig. 3):…”
Section: The Global Scheme Of a Monitoring Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of collaborative interactions aims at monitoring student's activity and assessing the performance of learning: Beatriz Barros and M. Felisa Verdejo (Barros and Verdejo, 2000) analyzed student's interactions to improve collaborations; Juan (Juan 2008) developed an information system to monitor the student's activity in online collaborative learning; Putambekar (Putambekar, 2006) aimed at knowing whether as the collaborative interactions evolve new ideas raise or the built knowledge is enriched; in a study made by Yang and Chang (Yang & Chang, 2012) it has been found that interactive blogs are associated with positive attitudes towards academic achievement.…”
Section: Cscl Systemsmentioning
confidence: 99%